HUBUNGAN PEMBERANTASAN SARANG NYAMUK DENGAN KEBERADAAN AEDES SPP. SEBAGAI VEKTOR PENYAKIT DEMAM BERDARAH DENGUE - Ewin Sadana Hutapea; Ridwan Balatif; Lambok Siahaan (Universitas Tadulako, 2022)
Objective:to determine the relationship between mosquito nest eradication and the presence of Aedes spp. as a vector of dengue hemorrhagic fever in the Asahan district. Methods:This research is an analytic observational type in a cross sectional design by determining the sample using the Slovin formula and the proportionate stratified random sampling method, because the population is heterogeneous. Assessment of PSN measures was measured using a questionnaire and the presence of Aedes mosquito larvae was known by direct inspection of the respondent's residence. Results:Respondents were dominated by women (59.6%) with the highest age range being 26-25 years (28.4%). Most of the respondents are high school graduates (38.9%) and work as housewives (52.4%). The PSN action of most of the respondents (77.1) was classified as good. From the results of calculating the presence of mosquito larvae density, it was found that the Density Figure (DF) of Asahan Regency was at level 4 which means the medium category. From the analysis of the relationship between PSN action on the presence of Aedes mosquito larvae, significant results were obtained (p= 0.001). Conclusion: There is a relationship between the eradication of mosquito nests and the presence of dengue hemorrhagic fever vectors in the Asahan district.